Profil Pengkajian Resep Racikan Pediatri Pasien Rawat Jalan di Rumah Sakit Umum Daerah Labuang Baji Periode Bulan Juni-Desember 2022 - Annisyah, Nur; Ririn, Ririn; Azizah, Rizqi Nur (Makassar Pharmaceutical Science Journal (MPSJ), 2023)
Prescription screening is one of the pharmaceutical services used to minimize the occurrence of errors in drug prescribing. The purpose of this study was to review the prescription of pediatric concoctions for outpatients in June-December 2022 at Labuang Baji Hospital based on Permenkes No. 72 of 2016 concerning Pharmaceutical Service Standards in Hospitals. non-experimental descriptive research with data collection was carried out retrospectively. The population in this study was 217 prescription sheets. The results showed the percentage of completeness of administrative aspects, namely patient name 98%, patient age 41%, gender 0%, body weight 25%, height 1%, doctor's name 91%, address and doctor's signature and license number 100%, prescription date 93%, prescription origin unit 95%. The suitability of the pharmaceutical aspects, namely the name of the drug, dosage form, amount of drug, rules and methods of use 100%, dosage strength 0%, no incompatibility, 35% hygroscopic & 65% photolysis. The suitability of clinical aspects, namely the accuracy of the indication and the accuracy of the time of use of 100%, there were no drugs that were duplicated, for the accuracy of the dose there were 9% overdose and 5% underdose. From the results of this study it can be concluded that the prescription at Labuang Baji Hospital has not fully met the suitability of the prescription based on Permenkes RI No. 72 of 2016 concerning Pharmaceutical Service Standards in Hospitals.